1999
DOI: 10.1177/009539999400935475
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Democracy and the Diffusion of Municipal Web Pages in California

Abstract: Although the Internet has been touted as a means to improve democratic governance, there has been little systematic analysis of its use. The authors analyze the diffusion of municipal Web sites that include information concerning a specific locality. The analysis is based on demographic and fiscal data from 454 California cities and two surveys of Web site adoption. The authors’ theoretical framework draws from the political economy and technology diffusion literatures. City size, government resources, concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 11 publications
4
68
1
4
Order By: Relevance
“…In general, large governments are more likely to adopt e-government than small ones because they operate under greater pressure to find alternative ways to provide public services (Moon and Norris, 2005;Weare et al, 1999;Musso et al, 2000;West, 2001). …”
Section: E-government Government Effectiveness and Institutional Chamentioning
confidence: 99%
“…In general, large governments are more likely to adopt e-government than small ones because they operate under greater pressure to find alternative ways to provide public services (Moon and Norris, 2005;Weare et al, 1999;Musso et al, 2000;West, 2001). …”
Section: E-government Government Effectiveness and Institutional Chamentioning
confidence: 99%
“…There has been research among local governments in, although not limited to, Brazil (Sugiyama, , 2012, the United Kingdom (Boyne, Gould-Williams, Law, & Walker, 2005;, the United States , and Denmark . Moreover, available subnational studies are heavily concentrated in the domain of egovernment innovations Weare, Musso, & Hale, 1999).…”
Section: Progress In the Selection Of The Empirical Domainmentioning
confidence: 99%
“…It has been often assumed that larger organizations have greater command over financial and human resources and are therefore more capable of adopting and implementing innovative practices Weare et al, 1999). For example, found that municipalities in California that adopted a website had larger populations, and also had significantly higher levels of government spending and revenues.…”
Section: Human and Financial Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger cities face a greater need for innovative solutions to address more complex policy problems. As a result, they are usually more willing to adopt innovative reforms or technological change [29,43,44].…”
Section: Research Hypothesesmentioning
confidence: 99%